UJI ORGANOLEPTIK DAN ANALISIS KANDUNGAN KIMIA PADA MI KERING DARI TEPUNG KULIT BUAH NAGA MERAH DAN TEPUNG KACANG MERAH - Intan Anggraweni; Desri Maulina Sari; Herpandi Herpandi; Yuliarti Yuliarti (Journal of Food Technology and Agroindustry, 2022)
Dried noodles are a food favored by the people of Indonesia. But in general, dry noodles contain low levels of fiber and protein. Fiber and protein levels in food are needed by the body. Sources of fiber and protein can be obtained from vegetable sources, namely red dragon fruit skin and red beans. Utilization of red dragon fruit skin flour and red bean flour in the manufacture of dry noodles can make the dried noodles a source of fiber and protein. This study aims to produce the best dry noodle formulation. This study is an experimental study using the Completely Randomized Design method (CRD). There are 4 additional treatment of red dragon fruit husks and red-bean flour on dry noodles, which are added to F0 (100% : 0% : 0%), F1 (70% : 15% : 15%), F2 (60% : 20% : 20%) dan F3 (50% : 25% : 25%). Analysis is made of organoleptic (hedonic) tests and laboratory tests (protein and fiber levels). The result of this research is that F1 is declared as the most preferred formulation because F1 has a brown color, no unpleasant aroma, slightly savory taste and chewy texture. Based on the nutrient content test, F1 has a protein content of 12.04% and a fiber content of 10.12%. So that the dry noodle formulation F1 was declared the selected formulation and had fulfilled the claim requirements as a food source of fiber and protein. Keywords: Dried noodles; Red Dragon Fruit Skin Flour; Red Bean Flour; Fiber; Protein